Time-resolved characteristics of laser induced breakdown spectroscopy on non-flat samples by single beam splitting. Issue 65 (28th October 2020) - Lei, Bingying; Xu, Boping; Wang, Jing; Li, Jing; Wang, Yishan; Tang, Jie; Zhao, Wei; Duan, Yixiang
Abstract : A single-beam-splitting approach was used to enhance the signal intensity of LIBS under the extreme condition of a laser beam grazing the surface of non-flat samples. We investigated the time-resolved characteristics of laser-induced plasma under single- and split beam modes. Abstract : A single-beam-splitting approach was used to enhance the signal intensity of LIBS under the extreme conditions of laser beam grazing of the surface of non-flat samples. Time-resolved spectra show that the laser-ablated plasma presents a stronger spectral intensity and a slower plasma decay in the split beam mode because of the higher laser irradiance. The temporal evolutions of signal enhancement factors indicate that the enhancement effect first rises and then drops with delay time and the maximum enhancement factor of Al plasma comes later than that of Cu plasma under the same laser energy. The mechanisms behind it are discussed. It is also found that the electron density exhibits a faster decay with delay time in the split beam mode, mainly due to the faster plasma expansion. And a slower increase of electron density with laser energy is observed in the split beam mode because of the plasma shielding effect.